2016
DOI: 10.1007/s10195-016-0415-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for distant metastasis of dermatofibrosarcoma protuberans

Abstract: BackgroundDermatofibrosarcoma protuberans (DFSP) may recur locally but rarely metastasizes. Fibrosarcomatous transformation in dermatofibrosarcoma protuberans (FS-DFSP) is said to have worse prognosis compared with ordinary DFSP (O-DFSP). Since DFSP rarely metastasizes, there have been few reports summarizing data on distant metastasis cases at single institution. The aim of this retrospective study is to review DFSP cases in order to analyze risk factors for metastasis.Patients and methodsThis retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 19 publications
1
33
1
4
Order By: Relevance
“…In our study, the majority of recurrent lesions also grew slowly at the beginning but on subsequent grew rapidly. K et al reported that patients with large lesions have a high possibility to be associated with FS-DFSP 13. Interestingly, in the present study, there was no significant difference in tumor size between recurrent FS-DFSP and recurrent O-DFSP.…”
Section: Discussioncontrasting
confidence: 50%
“…In our study, the majority of recurrent lesions also grew slowly at the beginning but on subsequent grew rapidly. K et al reported that patients with large lesions have a high possibility to be associated with FS-DFSP 13. Interestingly, in the present study, there was no significant difference in tumor size between recurrent FS-DFSP and recurrent O-DFSP.…”
Section: Discussioncontrasting
confidence: 50%
“…9,10,24 Criscito et al reported that survival was influenced by tumor size, but they did not analyze the relation between recurrence and size. 10,15,26 No metastases were identified in patients without FS changes in this series. 10,24 In the current study, only 4 patients (1.1%) developed distant metastases, indicating that larger DFSPs and those with FS changes are more likely to develop metastases versus smaller DFSPs and those without FS changes.…”
Section: Discussionmentioning
confidence: 52%
“…Other studies did not report a significant influence of tumor size on recurrences. 3,26 Metastases most often are located in the lung but, in this cohort, also were observed in other locations, such as the pancreas, liver, and bone. The risk of metastases in patients who have DFSP with FS changes has been described previously, but series on this subject are scarce and consist of limited numbers of patients or case reports.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations